Graft copolymerization of acrylonitrile onto torch ginger cellulose - Fazliyana Ahmad Zaki,; Ibrahim Abdullah, (Universiti Kebangsaan Malaysia, 2015)
Graft copolymerization of acrylonitrile onto torch ginger cellulose was carried out in an aqueous medium with ceric ion redox initiator. The optimum grafting parameters such as temperature, reaction time, ratio of monomer to cellulose addition and ceric ammonium nitrate (CAN) concentration were determined and a maximum graft yield of 40% was recorded. The graft copolymer was characterized and compared with untreated cellulose. A new absorption peak corresponding to the nitrile group of acrylonitrile was recorded by FTIR at 2244 cm-1 on the grafted cellulose. The morphology studies showed that the diameter and the surface roughness of grafted cellulose had increased as compared with the untreated cellulose. On the contrary, the grafting had resulted in lowering the crystallinity of the cellulose from 63 to 53%. The grafted cellulose produced a new derivative TG peak at 420°C and higher residual percentage than the untreated cellulose.